2016
DOI: 10.1016/j.cej.2016.05.116
|View full text |Cite
|
Sign up to set email alerts
|

A new route for the synthesis of La-Ca oxide supported on nano activated carbon via vacuum impregnation method for one pot esterification-transesterification reaction

Abstract: Advanced carbon nanorod promoted binary CaO-La2O3 system with improved physical properties, tailored surface morphology and chemistry were developed in vacuumimpregnating methods. The nanostructured catalyst (CaO-La2O3/AC nanocatalyst) was prepared to convert high FFA waste cooking oil into biodiesel via one step esterificationtransesterification reaction. The novel catalyst was characterized by FTIR, SEM, XRD, TGA, BET, TPD-CO2 and TPD-NH3. The high catalytic activity of the nanocatalyst was mainly depends on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 33 publications
2
35
0
Order By: Relevance
“…The results of BaCl2/CaO catalyst showed gradually reduced of surface area and pore volume upon increasing the Ba species concentration. The significant reduction in the S BET and V p for synthesized catalyst was due to the excess of active metals embedded into the channel of parent materials and incorporated into the pore of CaO [1]. The average pore size of the novel catalyst was 1.16 time bigger than that of the CaO catalyst, suggesting that the particles of the calcined and treated razor clam shell were packed much closer.…”
Section: Catalyst Characterizationmentioning
confidence: 89%
See 1 more Smart Citation
“…The results of BaCl2/CaO catalyst showed gradually reduced of surface area and pore volume upon increasing the Ba species concentration. The significant reduction in the S BET and V p for synthesized catalyst was due to the excess of active metals embedded into the channel of parent materials and incorporated into the pore of CaO [1]. The average pore size of the novel catalyst was 1.16 time bigger than that of the CaO catalyst, suggesting that the particles of the calcined and treated razor clam shell were packed much closer.…”
Section: Catalyst Characterizationmentioning
confidence: 89%
“…The increasing energy demand, depleting fossil fuels and environmental problem resulted from climate change by continues consumption of petroleum derived fuel, make challenges for the scientific community and the researchers worldwide today [1]. Among the options explored for alternative energy sources, biodiesel is one of the attractive alternatives due to its renewability, biodegradability, and non-toxicity [2].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanorods have attracted great interest from past few decades owing to their physical (particle size, shape, large surface area and greater pore size distribution) and chemical properties [16][17][18]. Nanorods made of carbon also known as "carbon nanorods" and "diamond nanorods."…”
Section: Carbon Nanorodsmentioning
confidence: 99%
“…In different study, it was reported that promoting Fe/Mn catalyst with different potassium ratios in the range of 0 -3.0 wt.% resulted in increased crystallite size of the catalyst and a decrease in BET surface area. The increasing of potassium content retarded the reduction of the catalyst due to the strong interaction of iron oxide with potassium oxide and affected active metal sites [3]. Gasoline content increased from 51 to 59 wt.% when potassium promotion of 0.2 wt.% took place, whereas further increase of potassium content 0.7, 1.5 and 3 wt.%, decreased gasoline selectivity to 50, 33 and 25 wt.% respectively [4].…”
Section: Introductionmentioning
confidence: 99%
“…The present work was conducted to study the performance of prepared mono and bimetallic catalyst of Co and Ni active metals supported by activated carbon on the Fischer-Tropsch reaction, and to investigate the influence of the corresponding metal loading ratios and operating conditions on the gasoline selectivity and carbon monoxide conversion. 3 ) with 65% purity was purchased from USA (J.T. Baker).…”
Section: Introductionmentioning
confidence: 99%